2021
DOI: 10.1177/03000605211014784
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine carcinoma of the larynx with Lambert-Eaton myasthenic syndrome: a rare case report and literature review

Abstract: This current report describes a rare clinical case of neuroendocrine carcinoma (NEC) of the larynx with associated Lambert-Eaton myasthenic paraneoplastic syndrome (LEMS). A 68-year-old male patient presented with severe dysphonia and dysphagia. He underwent a total laryngectomy and the excised lesion was extremely large. A pathological examination demonstrated ‘morphological findings of a poorly differentiated carcinoma (G3) with aspects of neuroendocrine differentiation’ (i.e. a poorly differentiated neuroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This finding is similar to the clinical features of our patient. Mesolella et al [ 26 ] also reported a patient with laryngeal neuroendocrine carcinoma who did not undergo EMG examination and did not have paraneoplastic or MG-related antibodies. LEMS was diagnosed based on typical symptoms of proximal muscle weakness and autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the clinical features of our patient. Mesolella et al [ 26 ] also reported a patient with laryngeal neuroendocrine carcinoma who did not undergo EMG examination and did not have paraneoplastic or MG-related antibodies. LEMS was diagnosed based on typical symptoms of proximal muscle weakness and autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a decrease in strength and physical resistance, which leads to difficulty in carrying out strenuous activities and, in more serious cases, even simple daily activities. Concern about one’s physical appearance and one’s voice is what most affects the psychological well-being of laryngectomy patients, leading them to maintain a distance from the world around them and to withdraw into themselves, thinking that other people find them unpleasant [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concern about one's physical appearance and one's voice is what most affects the psychological well-being of the laryngectomee patient, leading him to maintain a distance from the world around him and to withdraw into himself, thinking that other people find him unpleasant. [34,35] Consequently, although laryngeal cancer has a good cure rate, it is equally true that it disturbs the patient's psychological balance throughout his life, influencing his habits and constantly reminding him of the cancer experience, due to the permanent presence of the tracheostoma. [20,32,36] Considering this, it is correct to take note of the change in the quality of life of the laryngectomee patient, but, at the same time, also of the current therapeutic and rehabilitative supports, which allow to compensate for this handicap.…”
Section: Discussionmentioning
confidence: 99%